THE ALGORITHM OF CONTROL OF TECHNICAL CONDITION THE ONBOARD FLIGHT-NAVIGATION COMPLEX, TAKING INTO ACCOUNT THE INFORMATION REDUNDANCY OF THE COMPLEX (ABSTRACTS) - E. A. Bolelov; A. V. Tsykarev; A. V. Sbitnev (Научный вестник МГТУ ГА)
This paper considers a variant of the algorithm of control of technical condition of the onboard flight-navigation complex on the basis of the theory of Markov estimation of random processes based on the information redundancy of the complex.